Answer/Step-by-step explanation:
Slope (m) = ⅖
Point on the line passes through (a, b) = (-5, 6).
Equation of the line in point-slope form, y - b = m(x - a):
Substitute a = -5, b = 6, and m = ⅖ into y - b = m(x - a)
Thus:
y - 6 = ⅖(x - (-5))
y - 6 = ⅖(x + 5) (equation in point-slope form)
Equation of the line in slope-intercept form, y = mx + b:
Rewrite y - 6 = ⅖(x + 5) in slope-intercept form
Thus:
y - 6 = ⅖(x + 5)
y - 6 = ⅖x + 2
Add 6 to both sides
y = ⅖x + 2 + 6
y = ⅖x + 8 (equation in point-slope form)